GREEN CATALYTIC SYNTHESIS OF PHENPROCOUMON - CANDU, Natalia; TOMPOS, Andras; TÁLAS, Emília; TUDORACHE, Mădălina; COMAN, Simona Margareta (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The catalytic potential of triflate-based activated carbon composites has been investigated in phenprocoumon (C3-alkylated compound) synthesis, through the alkylation of 4-hydroxycoumarin with phenyl-ethyl-carbinol. The main reaction products are O- and C3-alkylated compounds. However, O-alkylated product is more easily produced to the detriment of the C3-alkylated compound, the selective synthesis of the last being a challenge in these conditions. Both the conversion of 4-hydroxycoumarin and the selectivity to C3-alkylated compound is highly influenced by the physico-chemical characteristics of the catalysts and the reaction conditions. The highest 4-hydroxycoumarin conversions (16.0-30.0%) and selectivity to phenprocoumon (94.0-99.7%) were achieved with triflate-based activated carbon composites, characterized by the existence of strong Brønsted acid sites, optimal Lewis/Brønsted acid ratio, and bimodal micro-/mesoporosity.